The Meaning of Mood – Embedded Clauses in Spanish as a Case in Point - Jensen, Helle Dam (HERMES - Journal of Language and Communication in Business, 2011)
Mental space theory is a cognitive framework that explains the interpretation of linguistic expressions: it explains how interlocutors get from input to output. Whereas in traditional semantics words are taken to possess a static, prefabricated meaning, cognitive frameworks take meaning to be the result of an interpretive process. This article explains how mental space theory can be used in an analysis of mood in embedded clauses in Spanish. It starts from the assumption that the meaning of mood is constructed by interlocutors in an interpretive process on the basis of information from the modal morphemes combined with information from the linguistic as well as the extra-linguistic context. The interpretive process is represented as a sequence of mental spaces which are linked and structured on the basis of information from language and context.